Bacteriophages as Potential Treatment for Urinary Tract Infections - Sybesma, Wilbert; Zbinden, Reinhard; Chanishvili, Nino; Kutateladze, Mzia; Chkhotua, Archil; Ujmajuridze, Aleksandre; Mehnert, Ulrich; Kessler, Thomas M. (Frontiers in Microbiology, 2016)
Background: Urinary tract infections (UTIs) are among the most prevalent microbial diseases and their financial burden on society is substantial. The continuing increase of antibiotic resistance worldwide is alarming so that well-tolerated, highly effective therapeutic alternatives are urgently needed. Objective: To investigate the effect of bacteriophages on E. coli and K. pneumoniae strains isolated from the urine of patients suffering from UTIs. Material and methods: 41 E. coli and 9 K. pneumoniae strains, isolated from the urine of patients suffering from UTIs, were tested in-vitro for their susceptibility towards bacteriophages. The bacteriophages originated from either commercially available bacteriophage cocktails registered in Georgia or from the bacteriophage collection of the George Eliava Institute of Bacteriophage, Microbiology and Virology. In-vitro screening of bacterial strains was performed by use of the spot-test method. The experiments were implemented 3 times by different groups of scientists. Results: The lytic activity of the commercial bacteriophage cocktails on the 41 E. coli strains varied between 66% (Pyo phage) and 93% (Enko phage). After bacteriophage adaptation of the Pyo phage cocktail, its lytic activity was increased from 66% to 93% and only one E. coli strain remained resistant. One bacteriophage of the Eliava collection could lyse all 9 K. pneumoniae strains. Conclusions: Based on the high lytic activity and the potential of resistance optimization by direct adaption of bacteriophages as reported in this study, and in view of the continuing increase of antibiotic resistance worldwide, bacteriophage therapy is a promising treatment option for UTIs highly warranting randomized controlled trials.